Scaffolding as Teachers’ Guidance Role in the Context of Constructivist Learning Approach - Esra Çakar Özkan (Journal of Educational Issues, 2024)
This research aims to determine teachers’ opinions about guidance roles in the constructivist teaching-learning process, the meanings they place on guidance role and the types of scaffolding they use. Phenomenological design (phenomenology), one of the qualitative research methods, was used in the study, and teacher’s guidance role/scaffolding was determined as the phenomenon of the study. The research was conducted with 15 teachers from different branches working in Burdur in the academic year of 2021-2022. A semi-structured interview form developed by the researcher was used as a data collection instrument in the study. The qualitative data obtained in the study were simultaneously coded and classified by two different researchers using descriptive analysis method. The findings revealed that teachers were aware of their guidance roles, but they could not fulfill these roles due to the intense and difficult content of the course, the lack of time and national high-stakes tests, and they saw themselves as leader/guide, manager/administrator and information provider in the teaching-learning process. In addition, teachers preferred operational scaffolding more and they do not prefer strategic scaffolding while using conceptual and metacognitive scaffolding in the teaching-learning process. The results were discussed in line with literature and some suggestions were presented.